Nonoutbreak Surveillance of Group A Streptococci Causing Invasive Disease in Portugal Identified Internationally Disseminated Clones among Members of a Genetically Heterogeneous Population - Friães, A. (American Society for Microbiology, 2007)
The typing of 160 invasive Streptococcus pyogenes isolates confirmed the importance of pulsed-field gel electrophoresis and multilocus sequence typing for defining clones. The results identified an extremely diverse population and highlighted the importance of both internationally disseminated and local clones not previously associated with invasive disease.